STUDI KASUS KERAPATAN JALAN HUTAN DI DUA PERUSAHAAN HUTAN DI JAMBI - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1992)
A study on the forest  road densities  was carried out at two logging companies in Jambi in 1990.  The objective is to find  aut the information of forest  road densifies realized by the companies. Data on area cut and road constructed  during the latest ten years felltng  blocks (from 1980/1981 to 1989/1990) were coilected. The results of the  investigation reveal that.:1.   Annually, the length of forest.roods built by A and B logging companies ranged from 2,000  to 13,000 m with an average of 6.050 m. and from  7, 600 to 19.800 m with an average of 12, 733 m. respectively.2.  Forest  road density  of each felling block at A and B logging companies ranged from 2. 10 to 20 m/ha with an average of 8. 54 m/ha, and from 3.45  to 22 m/ha with anaverage of 10.02 m/ha, respectively.3.  The level of forest road density average in the two logging  companies was still bellaw those level based on Segebaden Formula.4.  It is suggested that log potential,  rood construction cost and skidding cost be taken info consideration in constructing ofrest road.